PENGARUH PEMBERIAN TEHNIK RELAKSASI TERHADAP TEKANAN DARAH TINGGI PADA PASIEN HYPERTENSI DI DESA MANJUNG - Purwandari, Kristiana Puji; Endarwati, Netik (Jurnal AKPER GSH, 2019)
Hypertension is a disorder of the circulatory system, which is quite disturbing to public health. In non-pharmacological therapy, one of the strategies to lower blood pressure is deep breathing exercises. Deep breathing exercises are soul and body relaxation that can be added to a variety of routines for a relaxing effect. The purpose of this study was whether there was an effect of deep breathing exercises on changes in blood pressure in hypertensive patients in Manjung Village, Wonogiri District, Wonogiri Regency. This study used a Quasi Experiment Design with a Control Time Series Design research design, where in this study two groups were divided into an experimental group and a control group. The sample of this study was 80 respondents, of which 15 respondents became the treatment group and 15 respondents became the control group. The data processing technique uses the Wilcoxon Test analysis technique and the Mann-Whitney Test, where HÎ¿ is rejected if the p-value is â‰¤ 0.05. This study showed that the cytolic and diastolic blood pressures in the experimental group showed a significant decrease before and after deep breathing exercises, where the systolic p-value = 0,000 and the diastolic p-value = 0,000. While the comparison between the experimental group and the control group during the post test there was a comparison where in the experimental group the blood pressure decreased while the blood pressure in the control group had systolic p-value = 0.003 and diastolic p-value = 0.000. This study was to determine the effect of deep breath relaxation techniques on high blood pressure in hypertensive patients. Hypothesis testing was carried out on hypertension patients using deep breath relaxation techniques in the treatment group and the control group. The conclusion is that there are differences in blood pressure in hypertensive patients after doing deep breathing exercises.